2022
DOI: 10.3390/ijms231911525
|View full text |Cite
|
Sign up to set email alerts
|

Directional Submicrofiber Hydrogel Composite Scaffolds Supporting Neuron Differentiation and Enabling Neurite Alignment

Abstract: Cell cultures aiming at tissue regeneration benefit from scaffolds with physiologically relevant elastic moduli to optimally trigger cell attachment, proliferation and promote differentiation, guidance and tissue maturation. Complex scaffolds designed with guiding cues can mimic the anisotropic nature of neural tissues, such as spinal cord or brain, and recall the ability of human neural progenitor cells to differentiate and align. This work introduces a cost-efficient gelatin-based submicron patterned hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…Scaffold stiffness is a central parameter in tissue engineering since it influences the differentiation and maturation of cells, e.g., cardiomyocytes differentiate and mature best when embedded in a matrix with E-modulus of around 11 kPa [ 25 ], while neuronal cells prefer scaffolds with 20 kPa [ 26 ]. The stiffness of the MCG bioink can be tuned by the concentration of TG.…”
Section: Discussionmentioning
confidence: 99%
“…Scaffold stiffness is a central parameter in tissue engineering since it influences the differentiation and maturation of cells, e.g., cardiomyocytes differentiate and mature best when embedded in a matrix with E-modulus of around 11 kPa [ 25 ], while neuronal cells prefer scaffolds with 20 kPa [ 26 ]. The stiffness of the MCG bioink can be tuned by the concentration of TG.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogels with a modulus of approximately 20 kPa demonstrated the most optimal performance in providing a conducive loading environment for cellular activities, further supporting nerve tissue regeneration. 94 Moreover, protein-based hydrogels have been successfully employed in nerve repair and regeneration efforts following ischemic stroke. For instance, fibrin glue subdural transplantation of induced pluripotent stem cells has shown promising results in improving focal ischemic injury, leading to the restoration of neurological and behavioral functions, and providing neuroprotective effects.…”
Section: Different Functions Of Injectable Hydrogels In Nerve Repair ...mentioning
confidence: 99%
“…The findings demonstrated that in the absence of further functionalization, the fiber layers enhanced directed cell proliferation and neurite extension [ 155 ]. Recently, enzymatically cross-linked gelatin hydrogels with stiffness varying from 8 to 80 kPa were coupled with a sparse monolayer of PCL electrospun fibers [ 151 ]. Using electrospinning as a method to introduce anisotropic characteristics to the hydrogels, PCL fibers were spun on top of the gel in either a random or aligned way without appreciably changing the stiffness of the hydrogel substrate ( Figure 8 ).…”
Section: Design Of Composite Fibers For Brainmentioning
confidence: 99%
“…Using electrospinning as a method to introduce anisotropic characteristics to the hydrogels, PCL fibers were spun on top of the gel in either a random or aligned way without appreciably changing the stiffness of the hydrogel substrate ( Figure 8 ). On the fibrous hydrogel scaffolds, a human neural progenitor cell line attached, proliferated, and differentiated [ 151 ].…”
Section: Design Of Composite Fibers For Brainmentioning
confidence: 99%
See 1 more Smart Citation